PENGARUH PENGAWASAN TERHADAP KINERJA KARYAWAN PADA PT PERKEBUNAN NUSANTARA V PABRIK PALM KARNEL OIL TANDUN ROKAN HULU - Harwina, Yulia (Eko dan Bisnis: Riau Economic and Business Review, 2022)
This research was conducted at PT. Perkebunan Nusantara V PKO Tandun Rokan Hulu Factory. The purpose of this study was to determine the effect of supervision on employee performance at PT. Perkebunan Nusantara V PKO Tandun Rokan Hulu Factory. The population in this study were 38 people. In this study, sampling using the census sampling technique was 37 people. The data used are primary and secondary data with analysis using simple linear regression with the results of the equation Y = 13.043 + 0.843X The results showed that the t_count value for the monitoring variable was 5.590 while the t-table value was 2.03011, it can be concluded that the t-count value > the value of t table and also the value of Sig. smaller than 0.05, which is 0.000, it can be concluded that the supervision variable has a significant effect on employee performance. The results of the coefficient of determination obtained an R Square value of 0.472 which means the magnitude of the influence of the independent variable/work supervision on the dependent variable/employee performance is 47.2% while the remaining 52.8% is influenced by other independent variables not observed in this study